Rekonstrukcje szczęścia w społeczeństwie neoliberalnym: Prozak jako sposób na życie - Melosik, Zbyszko (Wydawnictwo Naukowe UAM, 2013)
The article is aimed at analysing the social role of Prozac in contemporary society, especially among Americans. Various contexts of this problem are considered against the background of the psychopharmacological happiness concept as well as of different neo-liberal anxieties. Also, some moral and social issues of Prozac use are taken into account.
Reconstruction of Happiness in a Neo-liberal Society: Prozac as a Way of Life
Keywords: Prozac; life style; psychopharmacology; neo-liberal anxiety; chemical self